2011
DOI: 10.1371/journal.pone.0029107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Exposure to Vector Bites and Antibody Responses to Mosquito Salivary Gland Extracts

Abstract: Mosquito-borne diseases are major health problems worldwide. Serological responses to mosquito saliva proteins may be useful in estimating individual exposure to bites from mosquitoes transmitting these diseases. However, the relationships between the levels of these IgG responses and mosquito density as well as IgG response specificity at the genus and/or species level need to be clarified prior to develop new immunological markers to assess human/vector contact. To this end, a kinetic study of antibody level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 53 publications
5
59
0
1
Order By: Relevance
“…Our results show hu-NSG mice produce cytokines mimicking this response when bitten by uninfected mosquitoes, and most of these cytokines were still detectable at day 32 postbite. At least 4 different mosquito salivary proteins have been shown to affect platelet, thrombin, or other clotting factor function (23). Increased cytokine production by splenocytes of mice bitten by A. aegypti and Culex pipiens mosquitoes has been reported even after 7 to 10 days, suggesting possible delayed or persistent immunomodulatory effects on platelet or T cell functions (63).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show hu-NSG mice produce cytokines mimicking this response when bitten by uninfected mosquitoes, and most of these cytokines were still detectable at day 32 postbite. At least 4 different mosquito salivary proteins have been shown to affect platelet, thrombin, or other clotting factor function (23). Increased cytokine production by splenocytes of mice bitten by A. aegypti and Culex pipiens mosquitoes has been reported even after 7 to 10 days, suggesting possible delayed or persistent immunomodulatory effects on platelet or T cell functions (63).…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentrations of SGEs were determined using a nanophotometer (Nanophotometer Implen P 360, Germany). Salivary gland extracts were then diluted in 0.1M bicarbonate buffer (pH 9.6) to obtain a protein concentration of 1µg/µL for enzyme-linked immunosorbent assay (ELISA) (11) .…”
Section: Salivary Gland Extraction and Protein Quantifi Cationmentioning
confidence: 99%
“…The immunogenicity of salivary proteins has been demonstrated in previous studies, which showed that salivary proteins can induce the host immune response by producing immunoglobulin G (IgG) and immunoglobulin E (IgE) via hypersensitivity reactions (9) . The presence of a specific IgG antibody response against whole saliva extracts (WSEs) of Anopheles METHODS mosquitoes can be measured by enzyme-linked immunosorbent assays (ELISAs) in children and adults exposed to mosquitoes bites (10) (11) . Additional studies have shown that the IgG response can recognize specifi c salivary proteins (12) (13) .…”
mentioning
confidence: 99%
“…sundaicus. SGPE consists of many different proteins, some of which can be conserved into genus and even family level (Fontaine et al 2011).…”
Section: Salivary Gland and Salivary Gland Proteinmentioning
confidence: 99%
“…aegypti and An. sundaicus belong to (Fontaine et al 2011). In this research, the grouping was based on age.…”
Section: Salivary Gland and Salivary Gland Proteinmentioning
confidence: 99%